Translation of Subtitle Texts by Visually Impaired Students: Process Analysis and Translator Subcompetencies - Suryaningtyas, Valentina Widya; Setyaningsih, Nina; Larassati, Anisa; Basari, Ahmad (Pusat Pelatihan, Riset, dan Pembelajaran Bahasa, 2023)
This article discusses the process of translating subtitles from English into Indonesian by visually impaired students. The approach used was a qualitative approach. Furthermore, this approach has two aspects of discussion, namely genetic (the translator) and objective (the translated text). First of all, the genetic aspect of this research is the translator sub-competence of visually impaired students. Furthermore, the objective aspect in this research is related to the translation process and the translations they produce. The data were collected using observation, true assignment, and recording techniques. Based on the research results, the translator’s sub-competencies include a) bilingual sub-competence; b) extralinguistic sub-competence; c) instrumental sub-competence; d) transfer sub-competence; e) strategic sub-competence; and f) psychophysiological components. To improve the quality of translation of visually impaired students, the researchers have compiled eight translation recommendations, such as translators must: pay attention to the suitability of the meaning of the source language, avoid omitting linguistic units, pay attention to word classes, and so on. Based on these recommendations, it is imperative that visually impaired students implement them in order to improve their capability as early-career translators.